Primary structure and function of a second essential member of the heterooligomeric TCP1 chaperonin complex of yeast, TCP1 beta. - Miklos, D (1994)
A role for heterooligomeric TCP1 complex as a chaperonin in the eukaryotic cytosol has recently been suggested both by structural similarities with other chaperonins and by in vitro experiments showing it to mediate ATP-dependent folding of actin, tubulin, and luciferase. Here we present the primary structure of a second subunit of the complex and present genetic and functional analyses. The TCP1 beta amino acid sequence, predicted from the cloned gene, bears 35% identity to TCP1, termed here TCP1 alpha, containing the same highly conserved residues found in the collective sequence of chaperonins. The predicted product was identified as the fastest-migrating species of the TCP1 complex purified from soluble extracts of yeast. The TCP1 beta gene, like TCP1 alpha, is essential. Strains containing lethal disruptions of either gene could not be rescued by additional copies of the other. Spores bearing disruption of either gene germinated as single, large-budded cells. Similarly, large-budded cells were observed following shift to 37 degrees C of strains carrying temperature-sensitive mutations in either TCP1 alpha or TCP1 beta. The arrested cells contained replicated DNA present in single nuclear masses, associated with abnormal tubulin staining patterns, supporting the assertion that mitotic spindle formation and function are impaired. We conclude that TCP1 beta supplies an essential function that partially overlaps with that of TCP1 alpha in acting as a molecular chaperone in tubulin and spindle biogenesis.